Transformation of councils for peoples’ health in federal setup in Nepal - Ranjit, Eurek; Dixit, Sanjaya Mani; Dixit, Hemang (Journal of Kathmandu Medical College, 2018)
The transformation of the country towards federalisation with seven federal provinces would require healthcare regulations and councils to be transformed accordingly. Attempts have been made to cover historical background, current scenario of Nepal, scenario in some other countries. Acts governing various councils of Nepal as well as other countries have been studied. Specific steps which would have to be addressed, amended and undertaken because of the federalisation have been pointed out. Areas which need to be addressed have been regarded as: composition of councils, licensure examination, establishment of institution in each province as well as whether or not to form the councils in each province.